Refractory humeral non-union: treatment with photodynamic intramedullary implant IlluminOss® and internal fixation - Basile, Giuseppe; Fozzato, Stefania; Bianco Prevot, Luca; Accetta, Riccardo; Petrucci, Quirino Alessandro (Acta Biomedica Atenei Parmensis, 2022)
Surgically treated humeral shaft fractures can develop into pseudoarthrosis (PSA). Even if PSA is treated according to the proposed literature, refractory non-union of the humerus can be determined. Due to the rarity of this condition, we report our experience in the management of refractory pseudarthrosis of the humerus at the IRCCS Galeazzi Orthopedic Institute (Milan, Italy). We used internal fixation with plate and screws associated with the implant of the IlluminOss® Photodynamic Bone Stabilization System to increase bone stability and improve anchoring of the implant medium. This combined treatment allowed the consolidation of the complex fracture despite the bone loss, ensuring excellent stability of the fracture stumps and constituting a flexible and stable system with the most favourable biomechanical conditions. An increase in refractory PSA cases is likely in the future, due to a higher incidence of surgically treated humeral shaft fractures than in the past. Further studies on the effectiveness of the combined use of plate and screw and the IlluminOss® system will be indispensable.